PECULIARITIES OF PROJECT –BASED LEARNING AS A MEANS OF DEVELOPING STUDENTS’ LIFE SKILLS METHODOLOGY - Tazbulatova G., Tazbulatova G.; L.N. Gumilyov , L.N. Gumilyov (Журнал иностранных языков и лингвистики, 2025)
The participants of the experiment were the second grade University students of the specialty “Foreign language: two foreign languages”.12 students took part in the experiment. The experiment lasted from autumn term for 15 weeks, from September till December 2023.The work program of the specialty “Foreign language: two foreign languages” provides five academic hours of Development of Oral skills per week. There was one group with intermediate language level. The age was mostly 17-19 years old. PBL was shown during the practical lesson on the board, main steps were explained. The topics for PBL were chosen according to the syllabus. Using different resources were also possible (Internet, magazines, books and other).